ANALISIS HUKUM ATAS PENERAPAN RAHASIA BANK DI INDONESIA TERKAIT DENGAN PERLINDUNGAN DATA NASABAH BERDASARKAN PRINSIP KEPERCAYAAN KEPADA BANK (STUDI PADA PT. BANK CIMB NIAGA Tbk CABANG MEDAN) - John Bert Christian; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2016)
Abstract Bank secrecy is the concrete form of consumers’ data and deposits protection in which the bank secrecy is the application of the fiduciary principle by the bank. It is seen that the customers give their data and fund to be saved in the bank based on their trust that the bank will provide protection for their data and fund, and without this trust, the customers will not use the banking service. Therefore, banking secrecy keeps existing as long as the bank applies the fiduciary principle, and the fiduciary principle must be equally applied between the interest of  individual  protected based on the fiduciary principle and the public interest for law enforcement. This is reflected through the application of the relative bank secrecy which allows the access to open the bank secrecy. Even though the access to open the bank secrecy is allowed, but as to show how important the fiduciary principle stated in a legal certainty in the protection of customers’ data is, any violation of the bank secrecy will be sentenced either in the forms of imprisonment, fine and/or administrative penalty. The bank secrecy in Indonesia needs a more specific and detailed regulation which is strictly related to whether or not the permission from the Governor of Bank Indonesia is needed. The regulations of Bank Indonesia as the implementing regulations can eliminate the doubt and ambiguity in the application of bank secrecy and the banking is expected to be able to accommodate the provision related to bank secrecy and customers’ data protection through the SOP of respective bank. Keywords: Bank Secrecy, Fiduciary principle, Customers’ Data Protection